2014
DOI: 10.4049/jimmunol.1400347
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Macrophage Selenoproteins in Experimental Colitis

Abstract: Inflammation is a hallmark of inflammatory bowel disease (IBD) that involves macrophages. Given the inverse link between selenium (Se) status and IBD-induced inflammation, our objective was to demonstrate that selenoproteins in macrophages were essential to suppress pro-inflammatory mediators, in part, by the modulation of arachidonic acid metabolism. Acute colitis was induced using 4% DSS in wild type mice maintained on Se-deficient (<0.01 ppm Se), Se-adequate (0.1 ppm; sodium selenite), and two supraphysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 48 publications
7
83
0
Order By: Relevance
“…This could contribute to a decrease in DSS-induced inflammation due to selenium supplementation (data not shown). Recent studies from our laboratory have indicated that alternatively activated macrophages (M2) play an important role in protecting the colon from DSS-induced inflammation, under selenium supplemented conditions [27]. …”
Section: Resultsmentioning
confidence: 99%
“…This could contribute to a decrease in DSS-induced inflammation due to selenium supplementation (data not shown). Recent studies from our laboratory have indicated that alternatively activated macrophages (M2) play an important role in protecting the colon from DSS-induced inflammation, under selenium supplemented conditions [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Trsp knockout in myeloid lineages through a LysM-Cre driver led to increased oxidative stress, upregulated transcription of antioxidant enzymes, accumulation of reactive oxygen species, altered expression of extracellular matrix-related genes, and diminished migration through matrix [56, 59]. Furthermore, placing these mice on an acute DSS-induced colitis protocol resulted in worse colitis characterized by pronounced inflammation, neutrophil infiltration, edema, weight loss, shorter colon length, and expression of pro-inflammatory cytokines relative to WT mice treated with DSS [60]. While intestine epithelial-specific Trsp KO has not yet been described, these data suggest selenoprotein expression in myeloid-derived immune cells are potent suppressors of inflammation in the gut and likely contribute to inflammatory tumorigenesis.…”
Section: Investigating Selenoproteins Through Sec Trna Mutationsmentioning
confidence: 99%
“…In addition, a combination of Se and vitamin E was found to exert a protective effect in rats by increasing their overall antioxidant capacity and total thiol levels in the colon [13]. Epidemiological studies have reported reduced Se concentrations in patients with CD or UC [14,15], and clinical studies have evidenced lower blood Se concentrations in IBD patients [5,16,17,18,19]. Se may have a beneficial effect in IBDs by modulating gut inflammation in combination with the gut microbiota [15].…”
Section: Introductionmentioning
confidence: 99%
“…Se may have a beneficial effect in IBDs by modulating gut inflammation in combination with the gut microbiota [15]. Thus, an increase in selenoproteins deactivates the prostaglandin E 2 (PGE 2 ) secreted by macrophages [14] by changing macrophage polarization from the macrophage-1 (M1) to the macrophage-2 (M2) phenotype, which in turn decreases gut inflammation [20]. These results suggest that higher Se concentrations than are currently recommended may be beneficial for IBD patients.…”
Section: Introductionmentioning
confidence: 99%